1982
DOI: 10.3109/00365528209181037
|View full text |Cite
|
Sign up to set email alerts
|

Psychic Disturbances in Adult Coeliac Disease

Abstract: Adult coeliac patients living in a defined area of Sweden were examined for a history of major psychiatric illness occurring before the coeliac disease had been diagnosed. Eight of 42 patients without dermatitis herpetiformis (19%) and one medical control subject had attended a psychiatric clinic over a 10-year period for neurotic disorders (p less than 0.05), mostly depression. Our study shows that psychiatric illness may be severe in undiagnosed adult coeliac patients. It was found to be the commonest reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0
3

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(29 citation statements)
references
References 0 publications
3
23
0
3
Order By: Relevance
“…In this context, another finding of our study is the evidence of a degree of depressive and anxiety symptoms in CD patients, adding further support to the relationship between psychiatric disorders and CD [45], [46]. Major depression has been widely studied by TMS, which has confirmed the key role of the GABAergic dysfunction in the neurochemical pattern of depressed mood, as indexed by a reduction of both CSP and ICI [11], [47]-[50].…”
Section: Discussionsupporting
confidence: 77%
“…In this context, another finding of our study is the evidence of a degree of depressive and anxiety symptoms in CD patients, adding further support to the relationship between psychiatric disorders and CD [45], [46]. Major depression has been widely studied by TMS, which has confirmed the key role of the GABAergic dysfunction in the neurochemical pattern of depressed mood, as indexed by a reduction of both CSP and ICI [11], [47]-[50].…”
Section: Discussionsupporting
confidence: 77%
“…State anxiety was present in a higher percentage of CD patients with respect to controls, while trait anxiety was not significantly different between CD patients and healthy controls, indicating that anxiety could be related to the disabling symptoms present at the time of the clinical and psychometric observation and to a sense of being different with respect to healthy subjects [10] . In addition, CD patients compared to controls showed higher scores of depression scale, supporting the previous findings [6][7][8][9] .…”
supporting
confidence: 80%
“…Hans Asperger reported that children with celiac disease also often exhibit psychological problems (Asperger 1961). Anxiety, depression, epilepsy, severe progressive neuropathy, gait ataxia, and limb ataxia are also seen in adult patients with celiac disease (Hallert and Derefeldt 1982, Hadjivassiliou et al 2002, Bushara 2005, Fasano and Catassi 2005, Genuis and Bouchard 2010). In individuals with diseases/syndromes such as irritable bowel syndrome (IBS), ulcerative colitis and Crohn’s disease, psychiatric symptoms have also been reported (Ringel and Drossman 2001, Ringel and Drossman 2002).…”
Section: Introductionmentioning
confidence: 99%